(untitled) (Revista BOEM, 2025)
This work aims to present the work developed in a study and research group called EmecForm - Study and Research Group in Mathematics Education, Curricular Structure and Teacher Training from when it was created until the first doctoral research that is being developed. This group is linked to the Graduate Program in Science Teaching at Universidade Cruzeiro do Sul. The group proposes to study the role that Mathematics plays in the curricular structure of elementary and high school, in addition to studying the training of the teacher who teaches Mathematics. The first doctoral research projects being developed by the group are theoretically and methodologically aligned with the project entitled “TEACHERS AND CURRICULAR POLICIES: an analysis of the processes of conception, elaboration and implementation of Curriculum in a Habermasian perspective”. The research methodology used to analyze the projects is of a qualitative nature and the data collection instruments are of a diverse nature, ranging from open interviews and questionnaires to the analysis of curricular documents. The EmecForm group has participated in national and international events since its creation and its members have managed to publish works in important periodicals in the Mathematics Education scenario.